English Depiction of Given-New Information in Business-Scape in Padang: a Linguistic Landscape Exploration - Kamelia Sari; NFN Oktavianus; NFN Zulprianto; NFN Novalinda (Balai Bahasa Kalimantan Tengah, 2023)
This study aims at revealing English representation on the business signboards in some business centers in Padang. This research is a qualitative descriptive study that helps researchers to have a thorough analysis of the data. Linguistic landscape and visual semiotics theories proposed by Landry and Bourhis, Kress and van Leeuwen, and Scollon and Scollon are applied to discuss the results. The visual semiotics theory is specified for only composition, especially given and new composition. The study finds that there are 687 data with 957 compositions of given-new, ideal-real, and center-margin information. Among them are 54 (6%) given compositions and 221 (23%) new compositions. It indicates that the business owners in Padang mostly use English as a subordinate language on the signboard. The business owners use English on the signboards to give new information to promote their stores. Hopefully, this research can give more contributions to the linguistic landscape in Padang. It also can broaden the readers’ horizons about the language in public spaces, especially the language used in business areas.AbstrakPenelitian ini bertujuan mengungkap penggambaran bahasa Inggris pada papan nama bisnis di beberapa pusat bisnis di Padang. Penelitian ini merupakan penelitian deskriptif kualitatif yang membantu peneliti untuk melakukan analisis data secara mendalam. Teori lanskap linguistik dan semiotika visual oleh Landry dan Bourhis, Kress dan van Leeuwen, dan Scollon dan Scollon diterapkan untuk membahas hasil penelitian. Teori semiotika visual dikhususkan hanya untuk komposisi, terutama komposisi ‘given’ dan komposisi ‘new’. Penelitian ini menemukan bahwa ada 687 data dengan 957 komposisi informasi yang given-new, ideal-real, dan center-margin. Diantaranya, terdapat 54 (6%) komposisi given dan 221 (23%) komposisi new. Hal ini menunjukkan bahwa pemilik bisnis di Padang sebagian besar menggunakan bahasa Inggris sebagai bahasa pelengkap pada papan nama. Pemilik usaha menggunakan bahasa Inggris pada papan nama untuk memberikan informasi baru untuk mempromosikan toko mereka. Diharapkan penelitian ini dapat menambah kontribusi penelitian lanskap linguistik di kota Padang. Selain itu, penelitian ini dapat memperluas wawasan pembaca mengenai bahasa di ruang publik, khususnya di bidang bisnis.